Learning from Primary Health Care Centers in Nepal: reflective writings on experiential learning of third year Nepalese medical students - Dhital, Rolina; Subedi, Madhusudan; Prasai, Neeti; Shrestha, Karun; Malla, Milan; Upadhyay, Shambhu (BMC research notes, 2015)
Background Medical education can play important role in cultivating the willingness among the medical students to work in underprivileged areas after their graduation. Experiential learning through early exposure to primary health care centers could help students better understand the opportunities and challenges of such settings. However, the information on the real experiences and reflections of medical students on the rural primary health care settings from low-income countries like Nepal are still limited. The aim of this study is to demonstrate the learning process of the medical students through their reflective writings based on Kolb’s theory of experiential learning. Methods The students wrote their experiences, observations and reflections on the experiential learning from the primary health care centers on individual logbook as part of their community posting assignments. We analyzed the data of 50 logbooks through content analysis using Kolb’s experiential learning cycle as a theoretical framework. Results The students’ reflections are structured around the four main learning stages of Kolb’s experiential learning theory. Each learning stage consisted of different categories. The first stage consisted of concrete experiences on rural health and learning by doing. The second stage included their reflective observations on primary versus tertiary care, application of theoretical knowledge and role of supervisors. In the third stage, the students developed and refined their concepts on self-development, understanding reality, compassion and sense of responsibility. The final stage, active experimentation, included their immediate future plans, suggestions to improve curriculum, plans after becoming a doctor and suggestions to improve policies. Conclusion This study provided important insights on different stages of experiential learning of medical students on primary health care in low resource rural settings. Reflective writing of experiential learning could be an important step to address the gaps in medical education for resource constraint settings like that of Nepal and other low-income countries.